2020
DOI: 10.1136/bmjinnov-2020-000512
|View full text |Cite
|
Sign up to set email alerts
|

Comparing video consultation and telephone consultation at the outpatient clinic of a tertiary referral centre: patient and provider benefits

Abstract: ObjectivesTelephone consultations are frequently used in the outpatient setting in order to avoid unnecessary travel and to reduce hospital visit-related costs for patients. However, they are limited by the absence of non-verbal communication in contrast to video consultation. Little is known considering the possible advantages of using video consultation in comparison to telephone consultation according to both patients and healthcare providers.MethodsPatients with colorectal diseases were asked to choose bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…The forest plot in Figure 3 demonstrates that patients from both cohorts would prefer RA in the future. This is in line with other studies ( 20 , 21 ). Of the 6 studies, only the study by Sathiyakumar et al failed to demonstrate a preference for RA.…”
Section: Discussionsupporting
confidence: 94%
“…The forest plot in Figure 3 demonstrates that patients from both cohorts would prefer RA in the future. This is in line with other studies ( 20 , 21 ). Of the 6 studies, only the study by Sathiyakumar et al failed to demonstrate a preference for RA.…”
Section: Discussionsupporting
confidence: 94%
“…The main barrier was the absence of non-verbal communication, illustrating the importance of visual cues (eg, eye contact, smiling, body language) in nurturing a good relationship with a nephrologist. 27 …”
Section: Discussionmentioning
confidence: 99%
“…In our interviews, many patients showed curiosity towards implementation of video consultations (VC) to possibly alleviate the lack of non-verbal communication. Barsom et al 7 found that, according to previous studies, almost half of the patients preferred VCs over TCs to communicate with their surgeon because of the benefits of providing visual feedback. A qualitative study on VCs in primary care by Donaghy et al ,4 additionally found that these visual cues increased patients’ confidence in the consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine has been suggested to improve the efficiency of outpatient follow-up and also appeared to be a suitable tool for follow-up outpatient care in various chronic and oncological conditions 2–4. In patient surveys, the possibility of fair communication,5 high patient satisfaction and confidence in its quality were reported 6 7. The absence of travel costs and benefits of time saving for patients have consistently been identified as predominantly important benefits compared with face-to-face consultations (FtFCs) 4 8 9…”
Section: Introductionmentioning
confidence: 99%